Psychometric Properties of the Utrecht Work Engagement Scale (UWES-9) in a Sample of Active Health Care Professionals in Spain - Domínguez-Salas S; Rodríguez-Domínguez C; Arcos-Romero AI; Allande-Cussó R; García-Iglesias JJ; Gómez-Salgado J (Psychology Research and Behavior Management, 2022)
Sara Domínguez-Salas,1 Carmen Rodríguez-Domínguez,1 Ana Isabel Arcos-Romero,1 Regina Allande-Cussó,2 Juan Jesús García-Iglesias,3 Juan Gómez-Salgado3,4 1Department of Psychology, Universidad Loyola Andalucía, Dos Hermanas, Seville, Spain; 2Department of Nursing, University of Seville, Seville, Spain; 3Department of Sociology, Social Work and Public Health, University of Huelva, Huelva, Spain; 4Safety and Health Postgraduate Programme, Universidad Espíritu Santo, Guayaquil, EcuadorCorrespondence: Carmen Rodríguez-Domínguez, Department of Psychology, Universidad Loyola Andalucía, Avenida de las Universidades s/n, Dos Hermanas, Seville, 41007, Spain, Tel +34 955 641 600 (Ext. 2625), Email mcrodriguez@uloyola.esPurpose: The impact of the COVID-19 pandemic on the working, personal and health conditions of health professionals has been highlighted, although it is necessary to verify whether certain instruments used in research on this topic have sufficient psychometric support for their use. This need was the main motivation for undertaking the present study. We aimed to analyse the psychometric properties of the Utrecht Work Engagement Scale (UWES-9) in a sample of active health care workers during the pandemic.Patients and Methods: A cross-sectional study was conducted from March to August 2020 with 2326 active health care workers (78.7% women). The instruments that were applied included the UWES-9 scale, the Sense of Coherence scale (SOC-13), the Goldberg General Health Questionnaire (GHQ-12) and an item on self-perceived health.Results: The three-factor structure related to the correlation of pairs of errors presented the best fit. The reliability of the UWES-9 was highlighted by the adequate internal consistency of the items, the existence of invariance according to gender, and its convergent and discriminant validity.Conclusion: The findings of this work support the use of the UWES-9 to assess the work engagement of health personnel during the COVID-19 pandemic and identify it as an adequate measure of this psychological variable and the constructs that comprise it.Keywords: gender invariance, UWES-9, engagement, health care professionals, COVID-19, psychometric